PENGETAHUAN MASYARAKAT DESA SIDOHARUM KECAMATAN SEMPOR TENTANG ORAL ELEKTROLIT DALAM PENANGANAN DIARE - Khuluq, Husnul; Handayani, Eka Wuri (LPPM STIKES MUHAMMADIYAH GOMBONG, 2018)
Diarrhea is still a public health problem in developing countries such as Indonesia, because of the high morbidity and mortality. In Indonesia, 60 million cases of diarrhea sufferers are found each year, 70-80% are experienced by children under 5 years (Â± 40 million incidents). The cause of infectious diarrhea is rotavirus infection which is common in children 6-24 months, with the highest incidence at the age of 9 to 12 months. OTC drugs are drugs that are not under the supervision of a doctor, drugs in this class can be traded freely, without a doctor's prescription and can be purchased at pharmacies, drug stores or stalls, for example cold medicines, diarrhea drugs, ulcer drugs and skin drugs. The use of over-the-counter drugs often occurs in the community and can cause problems such as inaccurate doses and errors in drug selection. This research is an observational research with descriptive method. This study was conducted involving 89 respondents. The results showed that there were still many people who did not understand about oral electrolytes in the treatment of diarrhea.